Cerebral Arteriovenous Malformations in Pediatric Patients with Hereditary Hemorrhagic Telangiectasia: Re-evaluating Appearance, Bleeding Risk, and Treatment Necessity in a Selective Meta-analysis - Mueller, Oliver; Kasper, Ekkehard; Droege, Freya; Goericke, Sophia; Stein, Klaus-Peter; Sure, Ulrich (Journal of Pediatric Neurology, 2020)
Pediatric patients suffering from cerebral nidal arteriovenous malformations are a unique population due to the rare occurrence of the disease. Diagnosis of hereditary hemorrhagic telangiectasia (HHT) in children is a rare event and mainly restricted to coincidental detection from screening of possibly afflicted family members. In patients with HHT, it is well known that the incidence of cerebral vascular malformations (CVMs) is higher than expected when compared with the nonafflicted population. Even though CVMs comprise a variety of different distinct anatomical and radiographic entities (e.g., capillary telangiectasia, nidal arteriovenous malformation [AVM], cavernous malformation, dural or pial as well as mixed fistula, and vein of Galen malformation), they are mostly summarized and analyzed all in one category due to the low number of individual cases identified in single centers. Nevertheless, the best treatment algorithm will likely vary significantly between different CVMs as does the clinical presentation and the natural course of the CVM. It is therefore the objective of this article to focus on nidal AVMs in pediatric patients suffering from HHT. To this end, we performed a systematic selective literature research to estimate incidence, clinical and radiological appearance, as well as classification according to established grading system, and to evaluate the necessity of treatment of these lesions in light of their respective outcomes. Our line of arguments explains why we recommend to follow these lesions expectantly and suggest to keep pediatric patients under surveillance with sequential scans until they reach adulthood.
Keywords: arteriovenous malformation; angiography; pediatric; hemorrhage